The Compulsory Care Act: Early Observations and Expectations of In- or Outpatient Involuntary Treatment - Gemsa, Stephan; Noorthoorn, Eric O.; Lepping, Peter; de Haan, Hein A.; Wierdsma, Andre I.; Hutschemaekers, Giel J. M. (Frontiers in Psychiatry, 2022)
Background. January 1st, 2020 the Dutch Compulsory Care Act (WvGGZ) replaced the Special Admissions Act (BOPZ). Whilst the old law only allowed compulsory treatment in hospital, the new law allows it both in and outside the hospital. Moreover, new law prioritises the patient's own opinion on coercive measures. By following patients’ own choices, the Compulsory Care Act is hoped to lead to fewer admission days and less inpatient compulsory treatment in involuntarily admitted patients. Methods. We studied the seclusion and enforced medication events before and after January 1st 2020 using coercive measures monitoring data in a Mental Health Trust. Trends in hours of seclusion and number of enforced medication events per month from 2012 to 2019 were compared to 2020. We used Generalized Linear Models to perform time series analysis. Logistic regression analyses and Generalized Linear Models were performed to investigate whether patient compilation determined some of the observed changes in seclusion use or enforced medication events. Results. The mean number of hours of seclusion between 2012 and 2019 was 27,124 per year, decreasing from 48542 in 2012 to 21,133 in 2019, and to 3,844 hours in 2020. The mean incidence of enforced medication events between 2012 and 2019 was 167, increasing from 90 in 2012 to 361 in 2019, and then fell to 294 in 2020. In 2020, we observed 3844 hours of seclusion and 294 enforced medication events. Near to no outpatient coercion was reported, even though it was warranted. The time series analysis showed a significant effect of the year 2020 on seclusion hours (β= -1.867; Exp(β)=0.155, Wald=27.22, p=0.001), but not on enforced medication events (β= 0.48; Exp(β)=1.616, Wald=2.33, p=0.13). Discussion. There was a reduction in number of seclusion hours after the introduction of the Compulsory Care Act. The number of enforced medication events also increased from a very low baseline, but from 2017 onwards. To see whether these findings are consistent over time, they need to be replicated in near future. Conclusion. We observed a significant increase of enforced medication use and a decrease of seclusion hours. 2020 predicted seclusion hours, but not enforced medication events.